Heritabilities, genetic and phenotypic correlations between carcass and live animal traits in sheep - Menzies, C.S.; Ahlschwede, G.; Wheat, J.D.; Mackintosh, D.L.; Kropf, Donald H. (Kansas Agricultural Experiment Station, 2011)
Data was collected on 91 lambs of known breeding born during the fall, 1963. The lambs were from ewes in the original fine-wool flock and were sired by 10 performance-tested Hampshire rams. This was the ewes fifth lamb crop.
Keywords: Sheep; Carcass characteristics; Performance; Gain